2018
DOI: 10.1029/2017gb005710
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Particle Size, Ballast, Temperature, and Oxygen in the Sinking Flux to the Deep Sea

Abstract: The “transfer efficiency” of organic particles from the surface to depth is a critical determinant of ocean carbon sequestration. Recently, direct observations and geochemical analyses have revealed a systematic geographical pattern of transfer efficiency, which is highest in high latitude regions and lowest in the subtropical gyres. We evaluate the possible causes of this pattern using a mechanistic model of sinking particle dynamics. The model represents the size distribution of particles, the effects of min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

26
115
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(149 citation statements)
references
References 95 publications
(172 reference statements)
26
115
2
Order By: Relevance
“…We show that different combinations of these parameters result in markedly different shapes in the flux profile. Similar to Cram et al 13 , we find the 'transfer efficiency' to be highly sensitive to the remineralization rate and the particle size spectrum. Cram et al 13 found their model was less sensitive to the dissolved oxygen concentration -a factor we did not include in ours.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…We show that different combinations of these parameters result in markedly different shapes in the flux profile. Similar to Cram et al 13 , we find the 'transfer efficiency' to be highly sensitive to the remineralization rate and the particle size spectrum. Cram et al 13 found their model was less sensitive to the dissolved oxygen concentration -a factor we did not include in ours.…”
supporting
confidence: 88%
“…We find this approach instructive in that it allows us to examine the contribution of specific size classes. Hence, we present a derivation of the model, even though the steady-state aggregate flux profile solution is similar to what was proposed in previous studies 10,13 .…”
mentioning
confidence: 85%
“…Uncertainty in future projections of low O 2 regions is reflected in the ©2019. These model biases reflect the sensitivity of low O 2 regions to numerous biological influences, including microbial community structure (Penn et al, 2016), organic matter stoichiometry (DeVries & Deutsch, 2014), and the depth scale of its remineralization (Cram et al, 2018;Van Mooy et al, 2001). This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.…”
Section: Introductionmentioning
confidence: 99%
“…Although observations reveal two distinct hypoxic zones separated by the equator, many ocean models produce an OMZ that spans the entire eastern tropics (Figure 1; see also Cabré et al, 2015). These model biases reflect the sensitivity of low O 2 regions to numerous biological influences, including microbial community structure (Penn et al, 2016), organic matter stoichiometry (DeVries & Deutsch, 2014), and the depth scale of its remineralization (Cram et al, 2018;Van Mooy et al, 2001). Physical processes that ventilate the OMZs, including strong zonal circulation (Aumont et al, 1999;Dietze & Loeptien, 2013;Duteil et al, 2014) and associated isopycnal stirring (Getzlaff & Dietze, 2013;Gnanadesikan et al, 2013), are also poorly represented in coarse global resolution models.…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsic variability of export will be driven by variability in nutrient supply, phytoplankton growth, predator behavior, and aggregate formation that creates spatial heterogeneity and temporal intermittency in the POC flux (e.g., Abraham, 1998;Karl et al, 2003;Zehr et al, 2017). POC export is also influenced by particle size, density, morphology, lability, ecological interactions, and physical factors, all of which exhibit substantial spatial and temporal heterogeneity (Alldredge & Silver, 1988;Armstrong et al, 2001;Burd & Jackson, 2009;Cram et al, 2018;Mahadevan et al, 2012;Steinberg et al, 2000). The time lag between production of POC in the surface ocean and its subsequent export to depth (e.g., Karl et al, 2003;Estapa et al, 2015) introduces an additional source of variability to POC fluxes.…”
Section: Introductionmentioning
confidence: 99%